PENGARUH PENERAPAN METODE PEMBELAJARAN KOOPERATIF YANG BERPUSAT PADA MAHASISWA TERHADAP EFEKTIVITAS PROSES PENGAJARAN PENGANTAR AKUNTANSI - Az Zahra, Lulu Nandita (Jurnal Ilmiah Mahasiswa FEB, 2019)
The purpose of this research is to determine the effect of the application of student centered cooperative learning to the effectiveness regarding to Introduction Accounting teaching process. The sample used by researcher in this study were 145 Active Undergraduate students in the Accounting Department, Faculty of Economics and Business, University of Brawijaya who have taken an Introductory Accounting course in the 2018 odd semester.This study used a survey method to collect the data. The technique used to test the hypothesis is Simple Linear Regression Analysis. The results of this study shows that student centered cooperative learning method positively affects the effectiveness of Introduction Accounting teaching process.Â Keywords : Student-Centered Cooperative Learning Method, Effectiveness of teaching process, Introduction Accounting Course